Factors determining the survival of new companies - Marlena Cegiełka (Central European Economic Journal (CEEJ), 2020)
This article discusses the determinants of the survival of new companies, with particular emphasis on their sources of financing. We have analysed the impact of experience in the same focal industry, of having a competitive advantage and intellectual property rights (patents and trademarks) and of debt financing on the probability of a start-up's survival, using a logit model based on the Kauffman Firm Survey (KFS) database data covering 4,928 American companies which operated from 2004 to 2011. Additionally, we can demonstrate that start-ups that use debt financing have a better chance of staying in business. Factors such as intellectual capital and competitive advantage are also positively correlated with the prospects for start-up survival.
Keywords: M13; G30; 330; start-up; survival of new companies; sources of financing